Implementation of Hy-Bon Edugame Based on Gender of Students' Learning Interest In Hydrocarbon - Rokhim, Deni Ainur; Nora, Nora; Sari, Anggreani Puspita; Rokayah, Dede Yayah (J-PEK (Jurnal Pembelajaran Kimia), 2022)
This research is geared toward observational data, which aims to determine the increase in the interest in learning of male and female gender students in science material, especially low CHEMISTRY. The objectives to be achieved in this research are to determine the implementation of the quasi-experimental method of "Hy-bon" edugame based on gender on interest in learning and to determine the increase in student interest in learning based on gender in the "Hy-bon" edugame. This research was conducted at SMAN 3 Sidoarjo, precisely in grade 12 MIPA 7 with a total of 33 students. The results showed that the student response questionnaire had an overall assessment average of 82%, and the student learning interest questionnaire had an overall assessment average of 77%. From the research results obtained through interviews that female gender students have more interest in learning by using the edugame media "Hy-bon".